IMPLEMENTASI MANAGEMENT PEMBINAAN PROGRAM OLIMPIADE SAINS NASIONAL DAN KOMPETISI SAINS MADRASAH DI MAN 1 LAMPUNG TENGAH - Hidayanti; Muhammad Nazir; Junaidah; Yetri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the Implementation of Management of the National Science Olympiad Programme and Madrasah Science Competition at MAN 1 Lampung Tengah, this research uses a qualitative approach with a case study method, this research was conducted at MAN 1 Lampung Tengah in the odd semester of the 2023/2024 academic year. Data sources in the study used primary sources and secondary sources. Data collection techniques with unstructured observation and documentation. Data analysis techniques using data reduction, data presentation, conclusions, and data validity assurance techniques using source triangulation and technical triangulation. The results showed that the implementation of the OSN programme coaching management and Madrasah Science Competition at MAN 1 Lampung Tengah was quite effective. Although MAN 1 Lampung Tengah has committed to increasing student participation and achievement in the OSN programme and Madrasah Science Competition, further efforts are still needed to overcome these obstacles. These recommendations are expected to help MAN 1 Lampung Tengah to continue supporting the development of students' potential in science through the OSN programme and Madrasah Science Competition.